Nutrition from Insects: An Age-Old Vietnamese View versus the Modern World’s Perspective - Nguyen, Minh-Hoang; Vuong, Quan-Hoang (Unisia, 2024)
Due to the rising pressure from population growth and environmental crises induced by anthropogenic food production activities, the production and consumption of insects have been promoted internationally. The current paper discusses the nutritional and environmental benefits of insect consumption and the socio-cultural and psychological factors that constrain such a habit on an international scale. Then, some historical and cultural information regarding insect consumption in Vietnam is provided to highlight the potential of insect consumption standardization. Unlike those in Western societies, where people exhibit significant psychological resistance to the idea of consuming insects as food, Vietnam has a longstanding tradition of entomophagy that can be traced back to Hoabinhian culture from 20,000 to 7,000 years BP, resulting in far less resistance to this practice. Despite the lack of research on entomophagy, its practice had an early scientific foundation at the beginning of the 20th century thanks to the early contribution of Nguyen Cong Tieu, a leading Vietnamese agriculture scientist since the French domination period (1884-1945). Nevertheless, insects are commonly viewed as street food or regional specialties but not dietary food, and the perception that insects are “poor man’s diet” persists, which can hinder the standardization of insect consumption within Vietnamese society. To capitalize on the nutritional sources from insects, we suggest that insect-eating should be embraced as an expression of progressive culture for environmental sustainability, and more interdisciplinary research in emerging countries, like Vietnam, could be conducted for the sake of good.